Pengaruh Al-Manar (1898-1935) Terhadap Al-Imam (1906-1908) - Sarwan Sarwan (Universitas Islam Negeri Imam Bonjol Padang, 2010)
Magazine Al-Imam is published after Al-Manar. And Al-Manar ia published after Al-'Urwat al Wutsqa. Al-'Urwatul Wusqo issued by Sheikh Jamaluddin al-Afghani and Sheikh Muhammad Abduh in Paris, France has succeeded in planting the seeds of modernization among Muslims worldwide. The spirit of Al-'Urwatul Wusqo forwarded by 'Abduh's disciple Rashid Ridho together with Al-Manar published in Egypt. Effect of Al-Manar Islam spread to various countries including the archipelago. The effect was taken by Sheikh Tahir Jalaluddin after completing his studies at Al-Azhar University in Egypt.